INTRA! INTRA! Towards an INTRA SPACE - Jauernik, Christina; Tschapeller, Wolfgang (Publication Series of the Academy of Fine Arts Vienna, 2021)
"INTRA! INTRA! calls a variety of thinkers to revisit INTRA SPACE, an artistic research project that experiments with the substances, constructions, and manifestations of our bodies in unchartered architectural waters of the near future. INTRA SPACE is a spatial, biological, technical and conceptual infrastructure for shared encounters with Carla, Dame (maybe Vivienne), Bob, Old Man and friends. INTRA SPACE is an experimental zone, set up to explore diaphanous relations between engineered virtual figures, humans, technical equipment and machines. Lingering between cameras, eyes, screens, mirrors and images of selves, this book is full of movement and flicker, of decreation, of dwelling at the periphery of someone else's vision, of resolutions beyond the eye/I. Strange encounters as springboards to unforeseen turns and perspectives. INTRA SPACE is the subject of this book, opening an arena for the companions and guests who walked in and out of this space in conversation with us. With contributions by Fahim Amir, Clemens Apprich, Esther Balfe, Gabrielle Cram, Dennis Del Favero, Ursula Frohne, Christina Jauernik, Vicki Kirby, Ludwig Löckinger, Hannes Mayer, Diane Shooman, Susanne Thurow, Wolfgang Tschapeller, Birk Weiberg, John Zissovici"